Foreign Capital and Colonial Development in Indonesia: A Synthesis - Jan Thomas Lindblad (Universitas Gadjah Mada, 2018)
This article discusses impacts of investment by foreign firms, in particular Dutch firms, on economy and society in Indonesia during the late colonial period (1910-1940) and immediately after independence (the 1950s). It starts out with a survey of the historiography, arguing that impacts of foreign investment on the host country have not been sufficiently specified in the literature. It offers a digression on the dimensions of foreign investment in colonial Indonesia as inferred from newly available primary data highlighting the chief characteristics of such investment. The article surveys a variety of economic and social impacts on the macro level and the level of individual regions and selected firms, focusing in particular on impacts that have so far received scant attention. A major conclusion is that positive gains did materialize in the host country, both economic and social, but also that the gains stayed short of what could potentially have been realized. The Dutch private firms investing in colonial Indonesia did display a measure of corporate social responsibility but their initiatives and efforts in that vein could have reached, considering the profitability of their operations. If so, they would have had a significantly larger impact on economy and society in colonial Indonesia.